Diagnostic Value of Superparamagnetic Iron Oxide Nanoparticles as a Tracer for Sentinel Lymph Node Mapping in Early-Stage Cervical Cancer: The Preliminary Clinical Experience - Marcin A. Jedryka; Andrzej Czekanski; Marcin Kryszpin; Tymoteusz Poprawski; Krzysztof Grobelak; Piotr Lepka; Rafał Matkowski (Journal of Functional Biomaterials)
Sentinel lymph node (SLN) mapping has been investigated as part of surgical staging in women with early-stage cervical cancer (CC); however, pelvic lymphadenectomy (PLND) remains the standard of care. This study aimed to assess feasibility and safety of SLN detection using superparamagnetic iron oxide (SPIO) nanoparticles as a tracer in CC. Thirty CC patients presumed to be stage I were included in this study with SPIO administered intracervically as a tracer for SLN mapping using a magnetometer and followed by PLND. The endpoints of the study included the proportion of successful SLN detection, the average number of SLNs per patient, and the proportion of pathologically positive results per patient and per node. The diagnostic accuracy of SPIO nanoparticles for detection of metastatic SLNs was evaluated by Receiver Operating Characteristic (ROC) curve analysis, with the area under the ROC curve (AUC) used to demonstrate the studied method’s sensitivity. Safety endpoints were a summary of all reported adverse events. SLNs were detected in all cases, bilaterally in 27 patients (90%). The median number of SLNs per patient was 3.5. Four cases had metastatic SLNs. The general malignancy rate per patient was 13.3%, and per node, it was 0.8%. The malignancy detection rate of SLNs was 100% per patient and 80% per node. The AUC of 1.0 (p < 0.001) confirmed the diagnostic value of the SPIO technique for the detection of metastatic SLNs, with a sensitivity of 100%. No adverse events related to the SPIO administration were reported. SPIO nanoparticles, as a tracer for SLN mapping in early-stage CC patients, demonstrated satisfactory accuracy parameters and safety; however, these data need to be evaluated by further research.